2019
DOI: 10.1007/s40120-019-0131-6
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy in an Elderly Population: Enhancing Medication Management Through the Use of Clinical Decision Support Software Platforms

Abstract: Introduction Polypharmacy is a growing problem in the United States. The use of multiple medications increases the likelihood that a patient will experience potential drug interactions and adverse drug reactions (ADRs). Those individuals with dementia or Alzheimer’s disease (AD) are at greater risk, due to age, comorbidities, and an increased likelihood of being on a greater number of neuroactive medications. Methods uMETHOD Health (uMH) has developed a precision medici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 40 publications
0
19
0
1
Order By: Relevance
“…This approach has to be examined over a longer period of time and further validated, including a broader variety of medications. Two studies [24,26] were identified as focusing on uncovering drug-drug interactions in patients on multiple medications. The developed scoring system from Duke et al 2010 [26] was evaluated in a pilot study and the results showed that using the application is 60% faster in searching for adverse events compared to traditional drug information resources.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This approach has to be examined over a longer period of time and further validated, including a broader variety of medications. Two studies [24,26] were identified as focusing on uncovering drug-drug interactions in patients on multiple medications. The developed scoring system from Duke et al 2010 [26] was evaluated in a pilot study and the results showed that using the application is 60% faster in searching for adverse events compared to traditional drug information resources.…”
Section: Discussionmentioning
confidence: 99%
“…The third study [24] included in this review also addresses interactions in medication plans. The results of the evaluation showed that older populations have a high medication burden and therefore medication management for polypharmacy is a challenging task.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The complexity of disease management in the presence of comorbidity and polypharmacy has been the focus of studies based on data analytics using ML/AI. For example, Keine and colleagues [19] investigated the effect of polypharmacy on older adults with dementia or Alzheimer's disease and predicted the medication burden using ML. Other investigators [20][21][22] raised computational challenges with predicting the effects of drug combination (both synergism and antagonism) and suggested ML as an effective method for tackling the challenge when data are available.…”
Section: Related Workmentioning
confidence: 99%